STUDIES ON THE TOXIC EFFECTS OF LEAD AND NICKEL MIXTURE ON TWO FRESHWATER FISHES, CTENOPHARYNGODON IDELLA AND HYPOPHTHALMICHTHYS MOLITRIX - S. Naz; M. Javed (Journal of Animal and Plant Sciences, 2013)
The Probit Analyses was used to determine the acute toxicity of binary mixture of lead and nickel for two fish species viz. grass carp (Ctenopharyngodon idella) and silver carp (Hypophthalmichthys molitrix). Correlation and regression analyses were also computed to find-out relationships among various parameters. The criteria of toxicity used during these experiments were mortality upon two fish species for 90-day. The tests were performed separately at constant pH (7), temperature (30°C) and hardness (200 mgL-1) of water with three replications for each test dose. There existed significant differences for LC50 and lethal responses for both grass carp and silver carp. The mean LC50 and lethal concentrations for grass carp were 56.422.51 and 120.987.18 while that of silver carp the same were 55.852.84 and 128.449.25 mgL-1 , respectively. Among two fish species silver carp was found significantly more sensitive in terms of 96-hr LC50 than that of grass carp. However, grass carp appeared significantly more sensitive than silver carp for lethal responses. The metallic ion concentrations of test mediums showed positively significant correlation with carbon- dioxide, sodium, potassium and electrical conductivity while inverse relationship was identified for dissolved oxygen for both fish species in the test media.
Keywords: Acute Toxicity; Metal Mixture; Lead; Nickel; Grass carp; Silver carp